Pengaruh Model Project Based Learning Berbantuan Media Video Animasi Terhadap Keterampilan Menulis Teks Puisi Siswa Kelas X Fase E di SMA Negeri 5 Padang - Aini Anggelika Putri; Andria Catri Tamsin; Afnita Afnita; Utami Dewi Pramesti (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE EFFECT OF THE PROJECT BASED LEARNING MODEL ASSISTED BY ANIMATED VIDEO MEDIA ON THE POETRY WRITING SKILLS OF GRADE X PHASE E STUDENTS AT SMA NEGERI 5 PADANG This study aims to analyze the effect of the Project-Based Learning (PjBL) model, supported by animated video media, on the poetry writing skills of Grade X (Phase E) students at SMA Negeri 5 Padang. The study employed a quantitative approach using an experimental method and a one-group pretest-posttest design. The population consisted of 397 Grade X (Phase E) students, while the sample comprised 40 students from class X-E.1, selected using purposive sampling. The research instrument was a poetry writing performance test, evaluated based on diction, figurative language, thematic relevance, and imagery. Data analysis involved normality tests, homogeneity tests, and hypothesis testing using the t-test. The results showed that the students' average poetry writing skill score prior to the implementation of the animated video-assisted PjBL model was 47.81 (classified as "Almost Sufficient"), whereas after implementation, it rose to 77.89 (classified as "Good"). Hypothesis testing revealed that the calculated t-value (15.31) exceeded the t-table value (1.69) at a significance level of 0.05, indicating a significant effect of the animated video-assisted PjBL model on students' poetry writing skills. Thus, the animated video-assisted PjBL model is effective as an alternative instructional approach for enhancing poetry writing skills in high school.